Assessment of Job Stress of Clinical Pharmacists in Ho Chi Minh City, Vietnam: A Cross-Sectional Study - Nguyen-Thi, Hai-Yen; Do-Tran, Minh-Thu; Nguyen-Ngoc, Thuy-Tram; Do, Dung Van; Pham, Luyen Dinh; Le, Nguyen Dang Tu (Frontiers in Psychology, 2021)
Objectives: The official implementation of clinical pharmacy in Vietnam has arrived relatively late, resulting in various stressors. This study aims to evaluate job stress level and suggest viable solutions. Methods: A cross-sectional study was conducted on clinical pharmacists (CPs) in 128 hospitals in Ho Chi Minh City (HCMC). Job stress questions were derived from the Healthcare Profession Stress Inventory (HPSI). Results: A total of 197 CPs participated, giving a response rate of 82.4%. Participants were found to have moderate job stress with an overall mean stress score of 1.5 (0.4) and stress rate of 52.8%. The sample size was statistically adequate and the HPSI was valid and reliable. Patient care responsibility was the main stressor, especially in public hospitals, followed by job conflicts. Lack of experience, low income, and inability to participate in clinical ward rounds caused significant stress to CPs regarding job recognition and job uncertainty. More practice-oriented training programs in bachelor curricula and clinical practice should be applied to help CPs gain more experience, self-confidence, and diminish job stress. Conclusion: CPs in HCMC have moderate stress. More practice-oriented training programs should be prioritized to lessen stress for CPs.